Measuring social, economic, policy, and health system determinants of maternal health and survival: An urgent global priority - R. Rima Jolivet; Jewel Gausman; Ana Langer (PLoS ONE, 2025)
In 2015, the World Health Organization (WHO) released global targets and strategies for reducing maternal mortality in the Sustainable Development Goal (SDG) period developed through broad stakeholder consultations. The targets and strategies identified in the “Strategies toward Ending Preventable Maternal Mortality (EPMM)” report are grounded in a systemic and human rights approach to maternal health and aim to address the broad spectrum of key social, political, economic, and health system determinants of maternal health and survival, as exemplified by 11 Key Themes. These upstream determinants of maternal survival are not well represented in maternal health measurement efforts, which tend to focus on service delivery. Thus, work was undertaken to develop a core set of maternal health indicators that could drive progress toward achieving the recommendations laid out in the EPMM Strategies that identified a menu of 25 indicators and 7 standard stratifiers related to the legal and policy environment, accountability mechanisms, inequities in access and quality, and empowerment of women, girls, families, and communities. Measurement experts have called for more research to ensure that indicators for monitoring maternal health, including its upstream determinants, are valid, which is critical if such measures are to be effective for driving and tracking progress toward ending preventable maternal deaths. This paper describes nine research reports emanating from seven discrete research studies to validate ten indicators in India, Ghana and Argentina that are compiled in a PLOS Collection with the aim of illustrating the breadth of the validation work, extracting some unifying themes and common findings, and discussing the implications for policy and practice they suggest.